2008
DOI: 10.1111/j.1365-2621.2007.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing and storage on the antioxidant activity of apple derivatives

Abstract: The antioxidant activity of seven apple varieties was determined on fresh fruits and processed products (driedfruits and purees) and during storage. The antioxidant activity of apples correlated with the total phenolconcentration but not with ascorbic acid concentration. Apple derivatives showed a lower antioxidantactivity than the counterparts of the fresh fruits and the occurrence of browning phenomena duringprocessing resulted in lower antioxidant activity. Dried fruits showed higher antioxidant activity pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
2
23
2
1
Order By: Relevance
“…5). Sacchetti et al (2008) reported an antioxidant activity increase within 30 days of storage at 20 C in dehydrated apple cubes, but then it declined thereafter. They suggest that this could be attributable to oxidation of polyphenols, such as catechin, leading to further polymerization into procyanidins, with higher antioxidant activities than the original substrate.…”
Section: Total Phenolics Antioxidant Activity and Antioxidant Capacitymentioning
confidence: 95%
See 3 more Smart Citations
“…5). Sacchetti et al (2008) reported an antioxidant activity increase within 30 days of storage at 20 C in dehydrated apple cubes, but then it declined thereafter. They suggest that this could be attributable to oxidation of polyphenols, such as catechin, leading to further polymerization into procyanidins, with higher antioxidant activities than the original substrate.…”
Section: Total Phenolics Antioxidant Activity and Antioxidant Capacitymentioning
confidence: 95%
“…Phenolic acids and flavonoids accounts for the majority of the antioxidant activity of apple fruit (Eberhardt, Lee, & Liu, 2000;Sacchetti et al, 2008). Quercetin glycosides and anthocyanins (cyanidin-3-galactoside) are the most abundant phenylpropanoids in apple peel, and not present in the flesh (cortex tissue) (Golding, McGlasson, Wyllie, & Leach, 2001;Tsao, Yang, Xie, Sockovie, & Khanizadeh, 2005;Wolfe, Wu, & Hai Liu, 2003).…”
Section: Total Phenolics Antioxidant Activity and Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the processing and storage may trigger the formation of new compounds having antioxidant properties. Products of the Maillard reaction, as a result of amino acid and saccharide condensation, are an example (Atrooz 2008; Sacchetti et al. 2008).…”
Section: Introductionmentioning
confidence: 99%